CATARACT SYMPTOMS SCALE AS A SCREENING TOOL FOR VISION DISORDERS DUE TO CATARACT BY NON-MEDICAL CADRES - Fauzie, Radityo Akhmedika (Majalah Oftalmologi Indonesia, 2023)
Introduction: Cataract is an eye disease with clouding of the lens causing visual interference. Blindness due to cataracts is still the leading cause of blindness in the world. Cataract screening using the questionnaire integrated interview method can be an easy instrument for non-medical cadres to use. Cataract Symptoms Scale (CSS) is a complaint-based questionnaire in cataract patients which is used to screen for visual disturbances due to cataracts. Objective: To find out whether CSS has good validity as a screening tool for visual impairment due to cataracts by non-medical cadres. Methods: This study used a diagnostic test to assess the accuracy of CSS. All respondents who met the inclusion and exclusion criteria were included as research subjects. Results: 151 respondents included in the vision screening activity of the Community Ophthalmology Unit of Cicendo Eye Hospital. Respondents with cataracts in this study amounted to 59 (39.07%) and non-cataracts amounted to 92 (40.93%). The most complaints of respondents were blurry with 145 complaints and the least complaints were changes in the color of objects, namely 36 complaints. The CSS questionnaire sensitivity value of 61.01% indicates a weak value statistically. The specificity value of 78.26% indicates a moderate specificity value statistically. The positive predictive value of 64.28% indicates a statistically weak NDP value. The negative predictive value of 75.78% indicates a statistically moderate value. The value of accuracy is 71.52% statistically moderate. Conclusions: The Cataract Symptoms Scale has poor validity to be used by non-medical cadres as a screening tool for patients with visual impairment due to cataracts. Further research is needed by adjusting the components of the questionnaire and adding variables such as visual acuity and cataract laterality.